Estandarización de procesos de productos lácteos mediante el desarrollo de fichas técnicas - Huayllasaca Belesaca, Ligia Esperanza (2018)
The present work talks about the standardization of the process of elaboration of the fresh cheese in the industrial plant ALIMEC SA since in the analysis of the information on claims of products of the line of dairy products, it was possible to determine that the fresh cheese has more frequency of claims, the claim that has greater incidence has the fresh cheese in the flavor, in the realized follow-up it was detected that the storage of the milk, the pasteurization of the milk, the process of salting and the stage of oreo are those that directly affect the flavor in the cheese, for this reason, the standardization of the process in its different stages is proposed, with the use of the DMAIC tool, which helps to create a culture of continuous improvement, in addition the collaboration of the creation of a trained sensory panel was used, helps assess what is the best standard that should be established in the cheese making process. At the end, a technical sheet is prepared with the parameters and standards that must be maintained in the process of making fresh cheese itself, which helps to minimize the risk of claims due to an uncommon flavor. It also helps to minimize the risks of faults in the others, stages of the process of making fresh cheese. The necessary recommendations are also made in order to make known to the different people working in the plant the advantages of standardizing the process and therefore the minimization of claims and therefore of costs and losses to the company ALIMEC S.A.